Vitamin D levels and platelet status in healthy children and adolescent - de Almeida, Pedro Antonio Souza; Oliosa, Polyana Romano; de Azevedo, Leticia Batista; Mill, José Geraldo; Barbosa, Miriam Carmo Rodrigues (Frontiers in Nutrition, 2025)
BackgroundRecent studies have expanded our understanding of the functions of vitamin D beyond bone health and calcium homeostasis. Limited data exists on the prevalence of vitamin D insufficiency in Brazil, particularly in children, but studies have shown deficiencies in a significant percentage of the population. Some studies have suggested a potential interaction between vitamin D and platelets, as they share common metabolic pathways, and alterations in platelet levels have been observed in individuals with vitamin D insufficiency.ObjectiveThis study aimed to verify if serum levels of 25(OH)D, platelet count, and mean platelet volume (MPV), are associated in children and adolescents aged 6 to 17 years old.MethodsThis is a cross-sectional study in children and adolescents aged 6 to 17 years (first sentence) Serra, Espírito Santo, a metropolitan city in Southeast Brazil. In total, 659 children and adolescents aged 6 to 17 years old and registered in a social project called “Estação do Conhecimento” in Serra, Espírito Santo, Brazil. Socioeconomic data were collected in the first interview using a semi-structured questionnaire. Blood was collected after 12 h of fasting, 25-hydroxyvitamin D [25(OH)D] levels were assessed using a chemiluminescence method, blood cells were analyzed using the counting method by impedance, and the cell analysis were performed by continuous flow cytometry.ResultsVitamin D insufficiency was highly prevalent among children and adolescents. Vitamin D levels and platelets were positively correlated and independently associated. Surprisingly, insufficient and deficient vitamin D were associated with higher mean platelet volume.ConclusionOur findings suggest that vitamin D’s influence on platelet parameters is likely indirect, possibly mediated by its role in modulating low-grade inflammation.